POTENSI SEGREGAN TRANSGRESIF BERDAYA HASIL TINGGI PADA BEBERAPA KOMBINASI PERSILANGAN GANDUM - Nurwanita Ekasari Putri; Surjono Hadi Sutjahjo; Amin Nur; Yudiwanti Wahyu; Trikoesoemaningtyas Trikoesoemaningtyas; Willy Bayuardi Suwarno (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
The need for domestic wheat grains tends to increase, and one of the efforts to face this situation is the assembly of tropical wheat varieties. The approach taken through this research is hybridization followed by several generations of selection. This study aimed to predict heterosis and the crossed combinations that possibly produced transgressive segregants. The experiment was conducted from August 2016 to May 2017 at the experimental station of the Indonesian Ornamental Plants Research Center, Cipanas (1100 m asl), Cianjur Regency, West Java Province. The genetic materials were seven genotypes, namely Guri1, Guri2, Guri3, Guri6, HP1744, IS-Jarissa, and Vee, crossed with the Selayar variety. This experiment used a randomized complete block design with three replications. The treatment was 15 wheat genotypes (seven F1 genotypes and eight parent genotypes), so there were 45 experimental units. There were yield and yield component observations. The results showed that several characters in each F1 combination of crosses had a higher or lower mean value than their parents. There is a combination of crosses that have a high heterosis value. The action of genes that control yield and yield components of wheat are overdominant, partially dominant, and partially recessive gene actions. The cross combinations of Guri3/Selayar, Guri6/Selayar, Jarissa/Selayar, HP1744/Selayar, and Vee/Selayar have a greater chance to produce transgressive segregants than the others.